SASSEN, SASKIA (2015). Expulsiones: brutalidad y complejidad en la economía global. Buenos Aires: Katz editores - Rojas, Luis Suárez (2020)
To better place the reader, it will be necessary to point out that the central core of his book addresses the perverse and contradictory side of globalization. However, it must be prevented, because you will not find here a hegemonic version of the subject, usually conceived as something abstract and omnipresent of forces. The author develops a rigorous sociology and does not trust any kind of canon, academic or theoretical fashion. On the contrary, his work is aimed at questioning the role of what he has called "master categories", noting their ability to illuminate and dull, placing certain aspects of reality in the shadow.